Systematic Review and Meta-analysis of Virtual Reality in Pediatrics: Effects on Pain and Anxiety - Eijlers, Robin; Utens, Elisabeth M W J; Staals, Lonneke M; de Nijs, Pieter F A; Berghmans, Johan M; Wijnen, René M H; Hillegers, Manon H J; Dierckx, Bram; Legerstee, Jeroen S (Anesthesia and analgesia, 2019)
Medical procedures often evoke pain and anxiety in pediatric patients. Virtual reality (VR) is a relatively new intervention that can be used to provide distraction during, or to prepare patients for, medical procedures. This meta-analysis is the first to collate evidence on the effectiveness of VR on reducing pain and anxiety in pediatric patients undergoing medical procedures. On April 25, 2018, we searched EMBASE, MEDLINE, CENTRAL, PubMed, Web of Science, and PsycINFO with the keywords "VR," "children," and "adolescents." Studies that applied VR in a somatic setting with participants ≤21 years of age were included. VR was defined as a fully immersive 3-dimensional environment displayed in surround stereoscopic vision on a head-mounted display (HMD). We evaluated pain and anxiety outcomes during medical procedures in VR and standard care conditions. We identified 2889 citations, of which 17 met our inclusion criteria. VR was applied as distraction (n = 16) during venous access, dental, burn, or oncological care or as exposure (n = 1) before elective surgery under general anesthesia. The effect of VR was mostly studied in patients receiving burn care (n = 6). The overall weighted standardized mean difference (SMD) for VR was 1.30 (95% CI, 0.68-1.91) on patient-reported pain (based on 14 studies) and 1.32 (95% CI, 0.21-2.44) on patient-reported anxiety (based on 7 studies). The effect of VR on pediatric pain was also significant when observed by caregivers (SMD = 2.08; 95% CI, 0.55-3.61) or professionals (SMD = 3.02; 95% CI, 0.79-2.25). For anxiety, limited observer data were available. VR research in pediatrics has mainly focused on distraction. Large effect sizes indicate that VR is an effective distraction intervention to reduce pain and anxiety in pediatric patients undergoing a wide variety of medical procedures. However, further research on the effect of VR exposure as a preparation tool for medical procedures is needed because of the paucity of research into this field.